2017
DOI: 10.4025/actascieduc.v39i4.33895
|View full text |Cite
|
Sign up to set email alerts
|

<b>Democracia y Educación presentes en las Reformas Educacionales Chilenas de los últimos 100 Años

Abstract: RESUMEN. Con motivo de la celebración del primer centenario de la publicación de la obra de John Dewey Democracia y Educación, se pretende mostrar cómo en los hitos más sobresalientes del desarrollo educativo de los últimos 100 años en Chile, especialmente en sus reformas, ha estado presente el afán democratizador impulsado por el educador norteamericano. En efecto, en el proceso de promulgación de la Ley de Instrucción Primaria Obligatoria de 1920, estuvieron presentes en el debate, las ideas de Dewey y, lo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the second chapter of his work, he highlights that the 1907 census, which showed that "60% of the total Chilean population and 52.8% of the population over five years old were illiterates" (D. Salas, 1967, p. 15). He then adds that the enactment of a law is not enough: More money from the state and more and better teachers are necessary, and parental neglect 8 must be overcome (Caiceo, 2017). Finally, in 1920, the Compulsory Primary Education Law was issued, establishing four years of mandatory education for all students and the commitment of the state to provide the necessary funding.…”
Section: Biography and Academic Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…In the second chapter of his work, he highlights that the 1907 census, which showed that "60% of the total Chilean population and 52.8% of the population over five years old were illiterates" (D. Salas, 1967, p. 15). He then adds that the enactment of a law is not enough: More money from the state and more and better teachers are necessary, and parental neglect 8 must be overcome (Caiceo, 2017). Finally, in 1920, the Compulsory Primary Education Law was issued, establishing four years of mandatory education for all students and the commitment of the state to provide the necessary funding.…”
Section: Biography and Academic Trainingmentioning
confidence: 99%
“…Salas, 1967, p. 15). He then adds that the enactment of a law is not enough: More money from the state and more and better teachers are necessary, and parental neglect 8 must be overcome (Caiceo, 2017). Finally, in 1920, the Compulsory Primary Education Law was issued, establishing four years of mandatory education for all students and the commitment of the state to provide the necessary funding.…”
Section: Darío Salas: An Exceptional Educatormentioning
confidence: 99%
See 3 more Smart Citations